Konseling Kelompok Melalui Tari Sambut dalam Meminimalisir Kecanduan Game Online pada Anak Sanggar Tari Seruni Palembang - Darmawani, Evia; Laksana, Robert Budi; Dedy, Adrianus (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The problems started covid while 19 have gone as well as learning during the learning offline, but affects the school age children including dancer seruni houses in palembang, usually school age children ranging from ( paud ) kanak-kanak park, primary school and secondary school first is cradled and berleha-leha by playing online games; mobile legend, free fore, school pubg mobile and neglect of duty, time interacting with keluarg, peer and other environmental. Conducted by penelitiuntukmembantupenari sehinggadiperlukansatuintervensi school aged by providing counseling groups through dance to welcome in minimize addicted to gaming houses onlline in palembang call seruni dance.This study attempts to attain further information about counseling group with a dancer in helping konseli tarisambut ( ) oneline addicted to break away from the game, besides mengenaliciri addicted to game oneline on dancer in a shrine seruni palembangpenelitiandilakukan seruni palembang dance in a shrine to the population and a dancer who trained dance to welcome were the; 10 6 4 the junior high school aged children and the primary school.Therefore, a intervention taken by the researchers to help the dancer in school age by providing group counseling through welcome dance in minimizing game addiction on lline on the balloon dance ring.The study aims to obtain further information about group counseling with welcome movements in helping counsel (dancer) get rid of online gam.Techniques of collecting observation and interview data (qualitative data) and scores of observation and interview results.Data analysis transforms qualitative assessments into quantitative. then calculate the average value of each aspect with the percentage formula, Interpretation of equal value qualitatively.Research results show that there are behavioral changes in children after performing dance therapy to cope with online gaming addiction.Children become more active and productive in dance activities and beneficial activities both at school and outside school in everyday life.Keywords: group counseling, addiction game on line, Dancing childrene addiction. In addition to analyzing online game addiction on the dancer in the seruni plays.The researchers performed in the balloon dance hall with a population and sample of dancer trained welcoming dancer trained in a total of 10 people; 6 children of the age of SMP and 4 people sd.Combined quantitative and quantitative research types with research and development approach